The packaging as an important part of the cosmetics process production - Jaśniewski, Piotr; Jakubowksa, Kinga; Sobiecka, Elżbieta (Biotechnology and Food Science, 2018)
This paper describes the cosmetic market development in Europe and in Poland. This review focuses on the last part of the cosmetics process production – confection, mostly on the packaging type materials, the function and design as well as the colour and information put on the labels. The packaging of the cosmetics influences the consumers decision concerning the choice and the purchase of the cosmetics. It is an important process which decides directly about the economy of the company